Evaluating Research Impact: The Development of a Research for Impact Tool - Tsey, Komla; Lawson, Kenny; Kinchin, Irina; Bainbridge, Roxanne; McCalman, Janya; Watkin, Felecia; Cadet-James, Yvonne; Rossetto, Allison (Frontiers in Public Health, 2016)
Introduction: This paper describes the development of a ‘Research for Impact’ Tool against a background of concerns about the over-researching of Aboriginal and Torres Strait Islander people’s issues without demonstrable benefits. Material and Methods: A combination of literature reviews, workshops with researchers and reflections by project team members and partners using participatory snowball techniques. Results: Assessing research impact is difficult, akin to so-called ‘wicked problem’, but not impossible. Heuristic and collaborative approach to research that takes in the expectations of research users, those being researched and the funders of research offers a pragmatic solution to evaluating research impact. The proposed ‘Research for Impact’ Tool is based on the understanding that the value of research is to create evidence and/or products to support smarter decisions so as to improve the human condition. Research is of limited value unless the evidence produced is used to inform smarter decisions. A practical way of approaching research impact is therefore to start with the decisions confronting decision makers whether they are government policymakers, professional practitioners or households and the extent to which the research supports smarter decisions and the knock-on consequences of such smart decisions. Embedded at each step in the impact planning, monitoring and evaluation process is the need for Indigenous leadership and participation, capacity enhancement and collaborative partnerships and participatory learning by doing approaches across partners. Discussion: The tool is designed in the context of Indigenous research but the basic idea that the way to assess research impact is to start upfront by defining the users’ of research and their information needs, the decisions confronting them and the extent to which research informs smarter decisions is equally applicable to research in other settings, both applied and theoretical. Beyond research, the tool can be adapted more broadly to prioritizing, monitoring and evaluating policies, services and programs. The authors are working closely with the Lowitja Institute staff to co-create and test the ‘Research for Impact’ Toolkit with Lowitja Institute-funded researchers and other research networks over the next two years (2016/17).